Pengembangan Produk Brownies Labu Kuning (Cucurbita Moschata) dengan Substitusi Pemanis Alami Daun Stevia (Stevia Rebaudiana) sebagai Pangan Fungsional: Product Development of Yellow Pumpkin (Cucurbita Moschata) Brownies with the Natural Sweetener Substitution of Stevia Leaves (Stevia Rebaudiana) as a Functional Food - Aji, Arif Sabta; Nurjanah, Raudah (Amerta Nutrition, 2025)
Background: Diabetes Mellitus is a global health problem. The prevalence of Type 2 diabetes mellitus (T2DM) in Indonesia reached 24.11%. High sugar consumption increases diabetes risk. Therefore, steamed brownies sweetened with stevia and pumpkin can be a healthy alternative snack. Objectives: To analyze the influence of the substitution of stevia sweetener and addition of yellow pumpkin in the steamed brownies product on water content, ash, nutritional value, total sugar, sensory evaluation, β-carotene, and antioxidant activity. Methods: This study used a single factor completely randomized design with four treatments: P0 (100% cane sugar and 0% stevia), P1 (50% and 50%), P2 (75% and 25%), and P3 (0% and 100%). Total sugar content was analyzed using the anthrone-sulfate test, antioxidant activity with 1-Diphenyl-2-Picrylhydrazyl (DPPH), β-Carotene using spectrophotometry, and sensory evaluation with the hedonic test. Data were analyzed using ANOVA and Duncan tests to determine the most significant treatment. Results: Substitution of cane sugar with stevia significantly affected the nutritional value, water content, ash, protein, fat, carbohydrate, and energy (p-value<0.001). β-Carotene levels and antioxidant activity also increased, with the highest levels in P3 (74.21 µg/100 g and 22.46%). Stevia affected the taste, aroma, and texture (p-value<0.001) but it’s not significant for color (p-value=0.712). Total sugar decreased with the addition of stevia (p-value<0.001). The IC50 results of antioxidant activity were very strong at 11.40 μg/mL. Conclusions: Using stevia in yellow pumpkin brownies (BrowPumpVi) reduces the total sugar content, increases antioxidant activity, and influences taste, aroma, texture, and β-Carotene levels but does not affect the color.